(untitled) (Annals of Medical Research, 2021)
Aim: Neonatal abstinence syndrome (NAS) is a clinical condition characterized by findings that develop after intrauterine exposure to addictive substances, especially opioids, and is characterized by signs related to the absence of the addictive substance in the postpartum period. Typically, NAS manifests in the first few days of life in the form of hypertonia, autonomic instability, irritability, poor absorption reflex, weight loss and, rarely, seizures. The present study was performed the clinical features of mothers who used addictive substances during pregnancy.Materials and Methods: Neonates born between September 2016 and December 2019 to opioid-addicted mothers and admitted to the neonatal intensive care unit (NICU) after birth for findings consistent with NAS were included in this study. The patients’ files were analyzed retrospectively. Maternal age, drug used/duration of use, smoking/alcohol use, the last time the substance was taken, gestational week of neonates, mode of delivery, birth weight, onset of NAS symptoms, highest Finnegan score, nutritional status, length of hospitalization, treatment duration and NICU follow-up data were recorded.Results: Nine babies were admitted to the NICU of follow-up for NAS symptoms. All mothers had heroin addiction. The median gestational week of the neonates was 37 (31-40) weeks and median birth weight was 2740(1530-3860) g. Median onset of symptoms was 2(1-4) days and the median Finnegan score of the patients was 10(3-17). Six (66.7%) neonates who did not recover with nonpharmacological treatment received phenobarbital therapy. Conclusions: For patients with NAS, phenobarbital therapy can be used as the first option when symptoms cannot be controlled by nonpharmacological methods in settings such as Turkey where oral morphine solution is not available. In our study, the symptoms were successfully controlled by phenobarbital therapy. However, more comprehensive studies are needed as there are insufficient data on long-term results.